Two decades of the Environmental Engineering in the view of graduates from Escola de Minas da Universidade Federal de Ouro Preto (Research, Society and Development, 2020)
Environmental Engineering, a relatively new type of engineering, still longs for more information on training and professional performance. Research with graduates can support this debate. This study presents exploratory and qualitative and quantitative research with graduates of Environmental Engineering from EM / UFOP regarding their perceptions about the course, the job market, and the relationship between the content received during graduation and the professional reality. The online questionnaire applied (survey method) identified the need to expand the articulation between theoretical content and real work situations - which corroborates the current trends in engineering education focused on a curriculum based on projects and other active methodologies. The articulation between the theoretical and practical content was also present in the reasons for increasing or decreasing the student's motivation during the course, in the suggestions for insertion of subjects, and the advice directed to the undergraduate students. Extracurricular activities stand out as an instrument for maintaining student motivation and facilitating their insertion in the job market. Graduates enter the market relatively quickly, with 50% of them starting to work in the field in less than 6 months after graduating. However, the largest portion (63%) receives less than the minimum wage. Average wages are higher among graduates with more experience. The results contribute to discussions about teaching Environmental Engineering, to promote the training of better prepared and safer professionals for professional coping.